Capturing the ephemeral human pluripotent state. Issue 7 (8th May 2016) - Ávila‐González, Daniela; García‐López, Guadalupe; García‐Castro, Irma Lydia; Flores‐Herrera, Héctor; Molina‐Hernández, Anayansi; Portillo, Wendy; Díaz, Néstor Fabián
Abstract : During human development, pluripotency is present only in early stages of development. This ephemeral cell potential can be captured in vitro by obtaining pluripotent stem cells (PSC) with self‐renewal properties, the human embryonic stem cells (hESC). However, diverse studies suggest the existence of a plethora of human PSC (hPSC) that can be derived from both embryonic and somatic sources, depending on defined culture conditions, their spatial origin, and the genetic engineering used for reprogramming. This review will focus on hPSC, covering the conventional primed hESC, naïve‐like hPSC that resemble the ground‐state of development, region‐selective PSC, and human induced PSC (hiPSC). We will analyze differences and similarities in their differentiation potential as well as in the molecular circuitry of pluripotency. Finally, we describe the need for human feeder cells to derive and maintain hPSC, because they could emulate the interaction of in vivo pluripotent cells with extraembryonic structures that support development. Developmental Dynamics 245:762–773, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: In this review we discuss the different human pluripotent stem cells derivate in vitro. The ground naive pluripotent state in human is still undefined as compared in mouse. There is a heterogeneity in profile expression and potential between different human pluripotent stem cells lines.